EFEKTIFITAS APLIKASI PERPAJAKAN E-REGISTRATION SEBAGAI SISTEM PENDAFTARAN NPWP ONLINE BAGI WAJIB PAJAK PRIBADI (STUDI KASUS DI KPP PRATAMA BEKASI UTARA) - Hoiriah Hoiriah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
e-Registration is one of system of taxation application that utilized for Taxpayer as [the] medium of Taxpayer registration online and system that utilized by Tax 0fficer, that to process data of Taxpayer registration begin at data input till pengaktivasi number of taxpayer fundamental (NPWP) and its card printing in North KPP Pratama Bekasi, or in any KPP. To assess effectiveness of taxation application e registration as [the] registration system NPWP Online is used model of combination research, consist of 8 variables laten are taken away from model testing DeLone and McLean (92;2003) that is variable ; Information Quality , System Quality, Quality Service, Usage, User Satisfaction , Clean benefits and research model Mahendra Adhi Nugroho (2008), that is variable of computer fear and Model Akbar and Parvez (2009) that is trust variable. Model Analyzer and hypothesis testing use Struktural Equatioan Modeling (SEM) and computer program from IBM AMOS VER. 19 and IBM SPSS Statistics VER. 19. Method that used [by] is spreading kuesioner with 150 sampel wajibpajaks person. Sampel that used [by] only 120 sampels. Research Result Taxation Aplication e-registration as system registration NPWP Online for private taxpayer effective because research model that analysed in full equation model structural is model that fit or good, valid factors and reliable and its variable each other has an effect on in significant.